Hemorrhagic bronchitis caused by carbapenem-resistant Acinetobacter baumannii infection: A case report - Zifang Li; Yu Sheng; Dongdong Huang (Respiratory Medicine Case Reports, 2024)
Carbapenem-resistant Acinetobacter baumannii (CR-AB) is rarely found in community respiratory infections, and there are currently no reports of hemorrhagic bronchitis caused by its infection. This work presents a case of bronchial bleeding in a diabetic patient who acquired a community-acquired infection of CR-AB. Treatment with levofloxacin was unsuccessful, as the patient's hemoptysis symptoms recur. The patient was treated with minocycline based on the drug sensitivity test, resulting in the disappearance of hemoptysis symptoms. The patient was subjected to follow-up by phone for three months and did not experience any further hemoptysis symptoms. This case highlights that CR-AB infection causes hemorrhagic bronchitis, and the antimicrobial treatment should be based on drug sensitivity results.